PENGARUH MEDIA BATANG CUISENAIRE UNTUK MENINGKATKAN KEMAMPUAN OPERASI HITUNG PENJUMLAHAN SISWA TUNAGRAHITA KELAS IV SDLB - Ria Sekarani; Wiwik Dwi Hastuti (Jurnal ORTOPEDAGOGIA, 2015)
ABSTRACT: Aims of this research are to describe: (1) capability of summation calculating operation for student with intellectual disability in the Grade IV of SDLB in baseline condition without using Cuisenaire batang media, (2) capability of summation calculating operation for student with intellectual disability in the Grade IV of SDLB in intervension condition using Cuisenaire batang media and (3) the influence of Cuisenaire batang media towards capability of summation calculating operation for student with intellectual disability in the Grade IV of SDLB. The result of the research showed that capability of summation calculating operation for student with intellectual disability is low before being given intervention and increasing after being intervention. The influence of Cuisenaire batang media as a form of intervention can be stated in calculation of overlap percentage between baseline phase 1 to intervention phase which is 0%.ABSTRAK: Tujuan penelitian adalah untuk mendiskripsikan: (1) kemampuan operasi hitung penjumlahan siswa tunagrahita kelas IV SDLB saat kondisi baseline tanpa menggunakan media batang Cuisenaire, (2) kemampuan operasi hitung penjumlahan siswa tunagrahita kelas IV SDLB saat kondisi intervensi menggunakan media batang Cuisenaire dan (3) pengaruh penggunaan media batang Cuisenaire terhadap kemampuan operasi hitung penjumlahan siswa tunagrahita kelas IV SDLB. Hasil penelitian menunjukkan, kemampuan operasi hitung penjumlahan siswa tunagrahita rendah sebelum diberikan intervensi dan meningkat saat diberikan intervensi. Adanya pengaruh penggunaan media batang Cuisenaire sebagai bentuk intervensi dapat dinyatakan dalam perhitungan persentase overlap antar fase baseline 1 ke fase intervensi sebesar 0%.